Correlation of Atopobium vaginae Amount With Bacterial Vaginosis Markers - Marconi, Camila [UNESP]; Cruciani, Frederica; Vitali, Beatrice; Donders, Gilbert G. G. (Lippincott Williams & Wilkins, 2012)
Objective. The purpose of this study was to test the correlation of the amount of Atopobium vaginae with the most commonly used markers for bacterial vaginosis (BV).Materials and Methods. We enrolled 103 nonpregnant and premenopausal women that were positive for BV by Amsel criteria and with a Nugent score higher than 3. All women were negative for yeast, Chlamydia trachomatis, Trichomonas vaginalis, and Neisseria gonorrhoeae. A. vaginae concentration was determined by quantitative polymerase chain reaction from samples of vaginal rinsings with 2 mL of sterile saline.Results. There was no difference in the median values of A. vaginae concentration when comparing samples with presence or absence of each individual Amsel criterion. In the case of a higher pH cutoff value of 4.9, greater amounts of this microorganism (p = .02) were found. In addition, correlation tests showed that A. vaginae concentration is positively correlated with pH (p < .001) and with Nugent scores (p = .003).Conclusions. The quantification of A. vaginae is useful for identification of the most severe cases of BV.
Keywords: bacterial vaginosis; Atopobium vaginae; quantitative polymerase chain reaction; lactobacilli; Gram stain